Morphological dependence of metal oxide photocatalysts for dye degradation - Naggar, Ahmed Hosny; Ahmed, Abdelaal S.A.; Seaf-Elnasr, Tarek Ahmed; Alotaibi, Nasser Fahad; Chong, Kwok Feng; Ali, Gomaa A.M. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
There is no doubt that organic dyes currently play an indispensable role in our daily life; they are used in products such as furniture, textiles, and leather accessories. However, the main problems related to the widespread use of these dyes are their toxicity and non-biodegradable nature, which mainly are responsible for various environmental risks and threaten human life. Therefore, the elimination of these toxic materials from aqueous media is highly recommended to save freshwater resources, as well as our health and environment. Heterogeneous photocatalysis is a potential technique for dye degradation, in which a photocatalyst is used to absorb light (UV or visible) and produce electron–hole pairs that enable the reaction participants to undergo chemical changes. In the past, various metal oxides have been successfully applied as promising photocatalysts for the degradation of dyes and various organic pollutants due to their wide bandgap, optical, and electronic properties, in addition to their low cost, high abundance, and chemical stability in aqueous solutions. Various parameters play critical roles in the total performance of the photocatalyst during the photocatalytic degradation of dyes, including morphology, which is a critical factor in the overall degradation process. In our article, the recent progress on the morphological dependence of photocatalysts will be reviewed.